2001
DOI: 10.1007/s002800100297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interval between the administration of doxorubicin and paclitaxel on the pharmacokinetics of these drugs in patients with locally advanced breast cancer

Abstract: Paclitaxel interferes with the pharmacokinetics of doxorubicin leading to higher systemic exposure to both doxorubicin and doxorubicinol, which is more evident when the plasma concentration of the anthracyclines is higher. This interference may explain the higher incidence of cardiac toxicity observed when the two drugs are administered within a short interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…A sophisticated pharmacokinetic study showed that PTX enhances the nonlinearity of DOX pharmacokinetics and significantly decreases the systemic clearance of both DOX and DOX-ol. The DOX/PTX interaction was found to be PTX-dose dependent, DOX concentration-dependent, and may be the result of competition for elimination mechanisms [48]. However, Platel et al [15] showed that the potentiation of DOX-induced cardiotoxicity by PTX is not related to an increase in tissue concentration of DOX or its active metabolite.…”
Section: Discussionmentioning
confidence: 97%
“…A sophisticated pharmacokinetic study showed that PTX enhances the nonlinearity of DOX pharmacokinetics and significantly decreases the systemic clearance of both DOX and DOX-ol. The DOX/PTX interaction was found to be PTX-dose dependent, DOX concentration-dependent, and may be the result of competition for elimination mechanisms [48]. However, Platel et al [15] showed that the potentiation of DOX-induced cardiotoxicity by PTX is not related to an increase in tissue concentration of DOX or its active metabolite.…”
Section: Discussionmentioning
confidence: 97%
“…The separate application of doxorubicin and paclitaxel at about a 16-h interval decreased the cardiotoxicity of doxorubicin in patients with locally advanced breast cancer. On the other hand, when doxorubicin and paclitaxel were applied at a shorter interval the cardiotoxicity increased (Moreira et al 2001). At present, there are more than 2000 safer and more effective synthetic analogues of doxorubicin, which are potential anti-tumour compounds, but only a small percentage of them have reached the registration or marketing phases (e.g., epirubicin, pirarubicin, idarubicin, valrubicin, Da-125) ( Figure 1) (Kim et al 2001;Grynkiewicz et al 2002).…”
Section: The Characteristics Of Selected Drugs Causing Multidrug Resimentioning
confidence: 99%
“…Taken together, these factors support the assumption that paclitaxel clearance did not vary much for any individual over successive cycles of treatment. Finally, while a pharmacokinetic interaction between doxorubicin and paclitaxel is possible, the literature suggests that while paclitaxel can alter doxorubicin pharmacokinetics, doxorubicin does not impact substantially on paclitaxel pharmacokinetics [43, 44].…”
Section: Methodsmentioning
confidence: 99%